Two methods of vibration perception assessing in workers exposed to hand-arm vibration - Zamysłowska-Szmytke, E.; Szymczak, W.; Śliwińska-Kowalska, M. (Archives of Acoustics, 2004)
It is known that vibration perception could be influenced by the device parameters and technique of measurement. The influence of confounding factors like age, weight and height on VPTs values was assessed in previous analyses in non-exposed subjects. The aim of present study was to compare the results of two techniques of vibrotactile thresholds measurement in workers exposed to hand-arm vibration. Two methods of vibration perception assessment were compared in 124 workers (21-62 years old, 1-40 years of employment) exposed mainly to hand-arm vibration during the work as: chain saw operator, pneumatic hammers operators, metal grinders, fitters, dentist technician. One method (named "standard method") has been used in Poland so far; the second one (named "according to ISO method") was established on the base of ISO Standard 13091-1-2001. The methods differed not only in technical parameters of stimuli but also in the way of normative values evaluation. In standard method there were no individual features or habits included. The results of investigation revealed that age and weight play the important role in interpretation of tests results, both in standard and according to ISO method. Moreover, standard method measurements seem to overestimate the number of subjects with recognized vibration sense abnormalities. In both methods exposure to vibration mostly could be revealed by stimuli at frequencies of 125 and 250 Hz.